Design model for the bending resistance of fibre reinforced glulam. (15th May 2020) - Blank, Lukas; Frangi, Andrea
Highlights: New, mechanic-based model to calculate the bending resistance of reinforced glulam beams. No use of empirical factors. Mechanic approach to consider the interaction of the reinforcement and the timber in the beam's tensile zone. Consistent approach to consider softening in the beam's compressive zone. Consistent consideration of the localisation phenomenon associated with softening behaviour. Good agreement of the new model with conducted large-scale and small-scale experiments. "Ready to use" formulation of the model. Abstract: A new model to determine the bending resistance of fibre reinforced glulam beams is presented. The model grounds on basic mechanical relations. New approaches are introduced to model the softening behaviour of the timber in the compression zone and the mechanical interaction of the reinforcement with the timber in the tension zone. This interaction considers the crack-bridging effect of the reinforcement. Localised phenomena such as the initiation of cracks in the tension zone or the formation of compression folds are modelled in a mechanical coherent way. In comparison with small-scale and full-scale experiments, the new model provides good results on both the characteristic as well as the mean level of the bending resistance. The new model is formulated in such a way that it can be implemented in a spreadsheet.